Effects of thorium and bromine on plant development and concentration of essential nutrients in wheat - Shtangeeva, Irina (Journal of Cereal Research, 2022)
Two greenhouse pot experiments were carried out to study the ability of wheat seedlings to accumulate thorium and bromine and estimate effects of the bioaccumulation of the trace elements on the plant development and concentrations of sodium, potassium and calcium. Wheat was capable of absorbing from contaminated soils large amounts of thorium and bromine. This resulted in variations in the plant biomass and concentrations of biologically essential nutrients. However, thorium and bromine caused different effects on the wheat seedlings